NASIONALISME-KEDAULATAN DALAM VISI PRESIDEN KE-1 SOEKARNO DAN PRESIDEN KE-8 PRABOWO SUBIANTO - Sabarudin, Didin (LEMBAGA PUSAT KAJIAN KEBANGSAAN/PUSKAB UKRI, 2024)
Nationalism and sovereignty are two words that are always attached to two figures of Indonesian national leaders, namely the 1st President Soekarno and the 8th President Prabowo Subianto. The nationalism and sovereignty echoed by the two Presidents are based on the empirical objective conditions faced by the Indonesian nation in the form of nationale geest (national spirit), nationale will (national will), and nationale daad (national action). Soekarno implemented nationalism and sovereignty based on the trisakti philosophy transformed by Prabowo Subianto during his administration with the symbol